THE EFFECT OF INBREEDING ON THE EARLY PERFORMANCE OF FRESHWATER PRAWN, Macrobrachium rosenbergii - Imron Imron (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2009)
Inbreeding depression has often been considered to be responsible for the deterioration of performance in aquaculture species. Despite a crucial impact that may result from inbreeding depression, comprehensive information reviewing this subject is limited. This study was aimed to gain information on the effect of inbreeding on the early performance of freshwater prawn. The study was performed by comparing performance of inbred and outbred populations. Inbred population was established by brother-sister mating (inbreeding rate of 25%) while the outbred population was formed by mating unrelated individuals. Several fitness and productivity related traits including survival, the rate of larval development, stage dispersion and growth of larvae were evaluated. Results suggest that inbred families performed poorer than that of the outbred in survival. However, inbreeding depression did not seem to occur in other traits including the rate of larval development, larval stage dispersion and growth. This study implies that to maintain genetic quality of farmed prawn stocks, inbreeding rate in farmed population must be controlled not to exceed that level. Implications that these findings may have on aquaculture practices and possible alternatives for the solutions are discussed.